EFFECT OF RETINAL THICKNESS VARIABILITY ON VISUAL OUTCOMES AND FLUID PERSISTENCE IN NEOVASCULAR AGE-RELATED MACULAR DEGENERATION: A Post Hoc Analysis of the HAWK and HARRIER Studies. Issue 3 (10th March 2022) - Dugel, Pravin U.; Jhaveri, Chirag D.; Chakravarthy, Usha; Wykoff, Charles C.; Singh, Rishi P.; Hamilton, Robin; Weissgerber, Georges; Mulyukov, Zufar; Holz, Frank G.
Abstract : Supplemental Digital Content is Available in the Text. In the HAWK and HARRIER studies, higher levels of variability in an individual's central subfield thickness measurements over the course of anti–vascular endothelial growth factor treatment were associated with poorer visual outcomes. Abstract : Purpose: To determine the association between central subfield thickness (CST) variability and visual outcomes in eyes with neovascular age-related macular degeneration treated with anti–vascular endothelial growth factor therapies. Methods: In this post hoc, treatment-agnostic analysis, patients (N = 1, 752) were grouped into quartiles of increasing CST variation. The association between CST variability and best-corrected visual acuity was measured from baseline, or from the end of the loading phase, until the end of the study using a multilevel modeling for repeated-measures model. The association between CST variability and the presence of retinal fluid was also assessed. Results: Increased CST variability was associated with worse best-corrected visual acuity outcomes at the end of study, with a least-square mean difference in best-corrected visual acuity of 8.9 Early Treatment Diabetic Retinopathy Study letters between the quartiles with the lowest and highest CST variability at the final visit. Increased variability was also associated with a higher mean fraction of visits with the presence of fluid. Conclusion: More stable CST was associated with better visual outcomes at the end of treatment suggesting that CST variability may provide a more reliable prognostic marker of visual outcomes than the presence of fluid alone, with the potential to enhance the clinical care of neovascular age-related macular degeneration patients.